New trends in process control and production management : proceedings of the International Conference on Marketing Management, Trade, Financial and Social Aspects of Business (MTS 2017), 18-20 May, 2017, Koesice, Slovak Republic and Tarnobrzeg - International Conference on Marketing Management, Trade, Financial and Social Aspects of Business (MTS 2017) (18-20 May, 2017 : Koesice, Slovak Republic and Tarnobrzeg, Poland); Stofova, Lenka; Szaryszova, Petra (Boca Raton : CRC Press, 2018)
"Global economic practice, progressive technical and system innovations in industry, business economics and production management in response to international strategic development documents and implementation of the best available techniques and technologies clearly induces the development trends of research and development, modernization of scientific infrastructure and improvement of overall conditions for research and development in process, financial and production management. Because of that there exist a place for examination and discussion on topics related to the state of art in business operations and their future development. The 5th International Scientific Conference was divided into two sections:1. Process and Financial Management2. Production Management. The emphasis in these sections was given in particular to increase competitiveness based on reducing costs toward the deployment of intelligent production systems, flexibility and innovativeness of producers. The conference was held under the patronage of the dean of the Faculty of Business Economics of the University of Economics in Bratislava with seat in Koaice, doc. RNDr. Zuzana Hajduova, PhD. This work holds the proceedings of the International Conference on Marketing Management, Trade, Financial and Social Aspects of Business, held May 18-20, 2017, in Koaice, Slovak Republic and Tarnobrzeg, Poland."--Provided by publisher.
Includes bibliographical references and index.
Also available in print format.
Keywords: Business -- Social aspects -- Congresses; Industrial management -- Congresses; Electronic books